Soil organic carbon depth distribution patterns in different land uses and management - Acosta-Mireles, Miguel; Paz-Pellat, Fernando; Hidalgo-Moreno, Claudia; Etchevers-Barra, Jorge D. (REVISTA TERRA LATINOAMERICANA, 2022)
The distribution of soil organic carbon (SOC) at depth is important to define carbon stocks and for analyzing the impacts of different destabilization mechanisms and processes. The modeling of the vertical distribution of the SOC has been approximated by empirical approaches or using first order kinetic models with multi-compartments. This paper introduces a kinetic model of n order, which generalizes previous developments of use of a single compartment. The model is adjusted to soil profiles of the Hillside Sustainable Management Project in the Sierra Norte of Oaxaca, Mexico, in three microbasins of the Mazateca, Cuicateca and Mixe regions. Sampling protocols, experimental design, systems and laboratory are presented. The kinetic model of n order was adjusted well to the experimental data (R2 > 0.99), although high variability (horizontal and vertical) was found, which was discussed as a possible relationship with the position of the field sampling points.